Smart tourism destinations: (Mis)aligning touristic destinations and smart city initiatives - Mariana Brandão Cavalheiro; Luiz Antonio Joia; Gabriel Marcuzzo do Canto Cavalheiro; Verônica Feder Mayer (BAR: Brazilian Administration Review, 2021)
Several tourism destinations around the world have started to implement smart city projects with the aim of improving the standard of living of their citizens, as well as the sustainability of their urban and touristic areas, which motivated the emergence of the concept of smart tourism destination. However, the extant literature on this subject is still incipient. Thus, this article aims to investigate, via an exploratory case study, whether the implementation of a smart city initiative in a touristic destination has helped it be transformed into a smart tourism destination. For that, a smart tourism destination development model is presented and applied as the theoretical lens adopted in this research. The results showed a clear misalignment between the smart city initiative and the touristic destination analyzed, as despite the opportunities arising from the technological infrastructure provided by the smart city project, the touristic sector of the city under analysis was not able to take advantage of the opportunities enabled by the smart city project. Lastly, one concluded that political discontinuity, missing local government tourism strategy and governance, lack of engagement of the citizens, and disregard for the local context were the main reasons for that misalignment.